Stakeholder relationship of household investments into residential building energy saving projects – modelling approach in the Hungarian case - Bíró-Szigeti, Szilvia; Vágási, Mária (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The paper presents the results of research focusing on residential energy saving investment projects of households in Hungary with the aim of identifying the relationship systems of stakeholders, based upon the stakeholder approach of the Overseas Development Administration (ODA) method. The research concept is based upon the need of identifying primary and secondary stakeholders, their resources, interests and conflicts, potential forces and weaknesses, and interactive relations that influence initiating and carrying out successful household building energy projects. Primary information is obtained from interviews with industrial experts and small enterprise owners and managers who are considered as authentic sources of knowledge about projects. The weaknesses of secondary sources also justify resorting to empirical research. The research findings are structured in the tables and figures as modelling tools and provide new research results. The modelling may serve as a practical instrument for the market actors and government decision makers and finally help to enhance energy saving opportunities
Argumenta Oeconomica, 2016, Nr 2 (37), s. 147-168
Keywords: Eastern European countries; energy industry; government policy; Hungary; stakeholders research